Kualitas Demokrasi untuk Lampung Berkompetensi - Ridwan Saifuddin (Inovasi Pembangunan : Jurnal Kelitbangan, 2017)
Democratization moveddynamically in Indonesia had initiated various impacts on each region level. In some regions, major or governor elected in direct election process was born leaderhaving effective leadership performance on public services. At the same time,in some regions the election didn’t change significantly with their new leaders. The hope to satisfy Lampung with competency should be supported by government competenceinresolving citizen problems. Acompetent government was expected to result from qualified democracy process. Through literature study, it would identify at least four factors which affected quality as resultedbythe democracy process of the major or governor direct election which werevoter preference quality, politician perception quality on problems and citizen aspiration he or she represented, bureaucracy (political) interest, and bureaucrat competency.